The McClellan report on the Italian-American Gangsterism (1965) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
The investigations of the Senatorial Subcommittee chaired by John McClellan (1963-65) were an important junction in the United States’ fight against organized crime. Beginning with the testimony of Joseph Valachi and at the initiative of Attorney General Robert Kennedy, the Subcommittee publicly highlighted the existence in the United States of a criminal association called Cosa nostra, formed by Italian-Americans and dedicated to the most varied activities. A summary of the context in which the investigations took place is proposed, followed by the first part of the Subcommittee’s final report.
Keywords: Joe Valachi, John McClellan, Cosa nostra, Organised Crime, United States of America